P121 Ambulatory Treatment For Pneumothorax: A Systematic Review of the Literature and Case For Outpatient Orientated Care?. (19th November 2012) - Brims, FJH; Maskell, N
Abstract : Introduction: Spontaneous pneumothorax (SP) is broken down into primary (PSP: no known underlying lung disease), secondary (SSP: known lung disease) and non-spontaneous from trauma or iatrogenic pneumothorax (IP). PSP carries a very low mortality. Current recognised treatments include a conservative approach, needle aspiration, intercostal chest tube (ICT) and surgery. A Heimlich valve (HV) is a lightweight one-way valve specifically designed for the ambulatory treatment of pneumothorax when used with an intercostal catheter. This systematic review was designed to examine the evidence for the use of HV in the management of adults with SP or IP. Methods: A systematic review was undertaken across nine electronic databases for studies reporting the use of HV for SP or IP. Randomised trials, case control studies and case series were included, unrestricted by year of publication. Post-thoracic surgery and traumatic pneumothorax reports were excluded. All publications were independently scored by two reviewers (FB & NM). Measures of interest included: the use of a HV alone to manage SP or IP, successful treatment as outpatient (OP), complications and financial data. Results: Eighteen studies were included reporting on the use of HV in 1235 patients, comprising 992 SP (of which 413 were reported as PSP) and 243 IP. The overall quality of the reports was low with only 2 RCTs (n=80 patients), 1 consecutive case series and 14 case reports. Table 1 presents a summary of the outcome measures. In some reports it was not possible to distinguish outcomes between pneumothorax type. There were highly variable protocols and treatment practise across the studies. No deaths were reported, complications included four haemothoraces and one chest wall haematoma. Three studies presented data with cost analysis, with OP HV vs. inpatient ICT cost ratios ranging from 1:3 to 1:5. Conclusions: High quality data to support the use of HV for ambulatory treatment of pneumothorax is sparse. There are, however, data on >1100 patients from case reports suggesting that the use of HV for SP and IP is safe, effective and may facilitate outpatient orientated treatment of pneumothorax. There is need for a carefully designed RCT to examine this further.